Press In Time of Mass Famine and Repression In Kasakh Land - Aldabergenov Қ.М. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The story analyzes the history of journalism in the thirty years of famine and repression, which is the «dark days» of the Kazakh people. For eight years, Goloshchyokin presented the program «Kishi Oktıabr» with the intention of returning socialism to Kazakh land in order to teach people «how to hold a spoon and a fork». As a result, at the beginning of 1933 half of the Kazakhs died and only 5 million animals out of 40 remained. This was called «minor» errors and «minor defects» until yesterday. The article is devoted to periodicals during the famine and repressions of the twentieth century, and also draws attention to its positive and negative trends.